PERSEPSI MASYARAKAT”TERHADAP KAWASAN TANPA ROKOK” (Studi Pada RT. 05 / RW. 05”Kelurahan Agrowisata Kecamatan Rumbai Barat) - Yona Kurnia; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
Non-smoking area, commonly referred to as KTR, is a room or area that is declared prohibited for smoking or producing activities, selling, advertising or promoting tobacco products. This study aims to determine: 1.) Public perception of a smoke-free area, (including location, mental readiness, emotional atmosphere, and environmental and social impacts) 2.) What factors influence people's perceptions of a smoke-free area (including internal factors, namely: feelings, attitudes, prejudices, and expectations, and external factors including background, information, family and knowledge) located in RT.05 / RW.05 Agrowisata Village, Rumbai District. The method used in this research is a quantitative analysis approach. The results obtained are 1.)People's perceptions of non-smoking areas are categorized as positive, because many people are awar “Of the dangers of smoking” and have high participation in these non-smoking areas.2.) Factors that influence people's perceptions of this smoke-free area are from oneself, family and from the surrounding environment       Keywords: Perception, Society, Non-Smoking Area